Bacterial contamination of colostrum fed to newborn calves in Québec dairy herds - Fecteau, Gilles (2002)
A convenience sample of 234 colostral specimens, collected directly from the nursing bottle immediately prior to the first feeding, was studied. Samples originated from 6 farms and were collected over 24 months. Routine bacteriologic techniques were used to quantify the bacterial load of the colostrum, as well as to identify the bacteria. Overall, at least 1 microorganism was cultured from 221 colostral samples (94.4%). By using the upper tolerance level of 100 000 bacteria/mL, 84 samples (35.9%) were considered contaminated. Staphylococcus spp. (57.7%), gram-negative rods (47.9%), coliforms (44.0%), and Streptococcus uberis (20.5%) were among the most frequently isolated bacteria. The relative risk (RR) of contamination with more than 100 000 bacteria/mL was significantly greater in warm months [RR = 2.55, 95% confidence interval (CI): 1.63 to 4.02] than in cool months and in colostrum offered to male calves (RR = 1.55, 95% CI: 1.09 to 2.20). Bacterial load was also associated with the farm of origin (P < 0.0001). When assessing colostrum management, one should consider bacterial contamination. Multiple factors are likely associated with the degree of contamination, and farm-specific factors may be important. Further studies are necessary to evaluate the impact of bacterial contamination of colostrum on neonatal health.